'Brand, community, lifestyle': Fashioning an authentic, body positive influencer brand on Instagram. Issue 4 (1st October 2022) - Brewster, Maureen Lehto; Sklar, Monica
Fashion influencers on Instagram create intimate and 'authentic' content to develop a branded persona, which they can use to build follower relationships and monetize their account through brand partnerships. However, some influencers are leveraging their online status and relationships to form their own fashion brands. This research examines three case studies of influencer-founded fashion brands: Day/Won, a size-inclusive athletic clothing company founded by model Candice Huffine; Premme, a plus-size clothing brand founded by fashion influencers Gabi Gregg and Nicolette Mason; and Megababe, a body positive beauty brand founded by fashion influencer Katie Sturino, to examine how they communicate with followers and reference body positive discourses to represent themselves as 'authentic' and inclusive brands. Over 500 Instagram posts from these influencers' personal and brand accounts were captured and manually coded and analysed using constructivist grounded theory for practices that the accounts used to establish authentic communication with followers. The findings suggest that influencer and brand accounts align their use of engagement, embodiment and expression strategies in order to develop and convey an authentically body positive identity.